响应面法优化重组谷氨酸棒杆菌G-BC 产脂肪酸的培养条件Optimization of culture conditions for fatty acid production of recombinant Corynebacterium glutamicum G-BC by response surface methodology - 杨青，孙子羽，满都拉，王佳，刘瑾，金晶晶，陈忠军 YANG Qing, SUN Ziyu, Mandlaa,WANG Jia, LIU Jin, JIN Jingjing, CHEN Zhongjun (Zhongguo youzhi, 2022)
乙酰辅酶A羧化酶是谷氨酸棒杆菌中调控脂肪酸合成的关键酶。为了研究乙酰辅酶A羧化酶α亚基（accBC）基因对脂肪酸合成的影响，以accBC表达的菌株重组谷氨酸棒杆菌G-BC为材料，研究了诱导剂异丙基-β-D-硫代半乳糖苷（IPTG）浓度、培养时间、培养温度对重组谷氨酸棒杆菌G-BC脂肪酸产量的影响，并通过响应面法优化了重组谷氨酸棒杆菌G-BC产脂肪酸的培养条件，同时与原始菌株脂肪酸产量进行了对比。结果表明：重组谷氨酸棒杆菌G-BC产脂肪酸的最佳条件为诱导剂浓度1 mmol/L 、培养时间20 h、培养温度32 ℃，在此条件下脂肪酸产量为34.56 mg/g（以菌体干质量计），比原始菌株提高了1.68倍。说明乙酰辅酶A羧化酶α亚基对于谷氨酸棒杆菌合成脂肪酸有促进作用。 Acetyl-CoA carboxylase is a key enzyme regulating fatty acid synthesis in Corynebacterium glutamicum. In order to study the effect of acetyl-CoA carboxylase α subunit (accBC) gene on fatty acid synthesis,the recombinant Corynebacterium glutamicum G-BC(expression strain of accBC) was used as raw material, the effects of inducer(isopropyl-β-D-thiogalactopyranoside,IPTG) concentration, culture time and culture temperature on the yield of fatty acid were studied. Moreover, the culture conditions for fatty acid production of recombinant Corynebacterium glutamicum G-BC were optimized by response surface methodology. The fatty acid yield of the original strain and the recombinant strain was also compared.The results showed that the optimal culture conditions were obtained as follows: inducer concentration 1 mmol/L, culture time 20 h, and culture temperature 32 ℃. Under these conditions, the yield of fatty acid was 34.56 mg/g（based on dry weight of bacteria）, which was 1.68 times higher than original strain. The accBC can promote the synthesis of fatty acid by Corynebacterium glutamicum.